2022
DOI: 10.3389/fpubh.2022.938770
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends in the Burden of Multiple Myeloma From 1990 to 2019 and Its Projection Until 2044 in China

Abstract: ObjectiveMultiple myeloma (MM) imposes a heavy burden in China. Understanding the secular trend of MM burden and projecting its future trend could facilitate appropriate public health planning and improve the management of MM.MethodsSex-specific incidence and mortality rates of MM in China from 1990 to 2019 were collected from the Global Burden of Disease 2019 study. The secular trend of MM burden was analyzed by joinpoint regression. Age–period–cohort model was used to analyze the effects of age, period, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The longer the follow-up duration is, the higher the possibility that salvage HDT/ASCT and the newest potent treatment regimens will be applied in the SDT/no ASCT group, which might reduce the OS difference between the 2 groups. It has been reported that older age is a crucial risk factor for elevated MM mortality, possibly due to deterioration of the general condition and intolerance to high-intensity antitumor therapy [ 38 , 39 ]. Previous studies also implied that males have higher incidence and mortality rates than females, which might be attributed to hormone differences and an increased probability of carcinogen exposure among males, such as smoking and alcohol [ 38 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The longer the follow-up duration is, the higher the possibility that salvage HDT/ASCT and the newest potent treatment regimens will be applied in the SDT/no ASCT group, which might reduce the OS difference between the 2 groups. It has been reported that older age is a crucial risk factor for elevated MM mortality, possibly due to deterioration of the general condition and intolerance to high-intensity antitumor therapy [ 38 , 39 ]. Previous studies also implied that males have higher incidence and mortality rates than females, which might be attributed to hormone differences and an increased probability of carcinogen exposure among males, such as smoking and alcohol [ 38 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that older age is a crucial risk factor for elevated MM mortality, possibly due to deterioration of the general condition and intolerance to high-intensity antitumor therapy [ 38 , 39 ]. Previous studies also implied that males have higher incidence and mortality rates than females, which might be attributed to hormone differences and an increased probability of carcinogen exposure among males, such as smoking and alcohol [ 38 , 40 ]. HDT/ASCT was reported to be effective for MM patients with both high- and low-risk genetic features [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, GBD data were calculated based on existing data of various countries by using algorithms. The accuracy of data depends to a large extent on the quality and quantity of the data used in the algorithm, which could affect the accuracy of the estimated burden ( 37 ). Second, data are sparse in representative regions and ethnic groups in many countries and age groups.…”
Section: Discussionmentioning
confidence: 99%
“…The Age Standardized Rate (ASR) for MM incidence was 1.78 per 100,000 individuals worldwide in 2020. Males were more likely than women to develop MM (ASR: 2.10), and men were also more likely to die from MM (ASR: 1.41) than women (ASR: 0.93) [6].…”
Section: Introductionmentioning
confidence: 99%